Roadway Deformation and Control under Multidisturbed Secondary High Stress - Xiaoguang Sun; Haibin Wang; Xiaofang Wo; Zhimeng Sun; Wenliang Sun; Chunge Li (Geofluids)
Aiming at the serious deformation and failure of mining roadway under the condition of high secondary stress in Xuchang Coal Mine, Shandong Province, the deformation law of surrounding rock under the influence of high secondary stress in the original support belt transport roadway was analyzed by the method of field measurement and numerical simulation, and the control scheme of surrounding rock was put forward. According to the actual site conditions of 3318 working face belt transport drift in Xuchang Coal Mine, this paper proposed a new bolt-net support technology scheme with high strength, high stiffness, and asymmetric characteristics and obtained through numerical simulation analysis: (1) when the 3318 working face begins to mining, the distribution of the maximum principal stress in the surrounding rock of the roadway changes from weak symmetry to strong asymmetry, especially the maximum principal stress in the surrounding rock of the two sides; (2) the superposition effect of leading abutment pressure, lateral abutment pressure, and fault structure has a strong influence on the distribution of the maximum principal stress of roadway surrounding rock. The field industrial test shows that the deformation of the surrounding rock at different parts of the belt transport roadway is significantly reduced after the implementation of the double-height asymmetric bolting support. Among them, the deformation of the roof decreases from 630 mm to 185 mm, the deformation of the left wall decreases from 550~620 mm to 150~170 mm, and the deformation of the right wall decreases from 600 mm to less than 180 mm. The nonuniform deformation degree of the top side is within 1~1.13, indicating that the anchor mesh composite bearing structure is uniformly deformed as a whole, and the overall bearing capacity of the structure is realized.